Influence of Employee Empowerment, Teamwork, and Incentive on Employee’s Job Satisfaction - Raime, Sharfika Binti; Ahmad, Siti Nor Bayaah; Nasirruddin, Md Saiful Anuar Bin Mohd; Ismail, Shahrizal Bin; Hakim, Anwar Redhwan Bin Lokman (American Journal of Social Sciences and Humanities, 2018)
The study on job satisfaction is important in the organisation. One of vital reason is that, job satisfaction is closely related to the job performance. People, who satisfy with their job tend to perform better in their works. How they feel about the work they are doing and the results received from that work directly impact an organisation’s performance and ultimately its stability. An improved job performance will as well reflecting the organisation performance, which later will result to cost effective and profitable business. The study was conducted in the background of one of Malaysian public service agencie located in northern regional of Malaysia. The data was analysed using SmartPLS 3.0 software. The study report has followed a descriptive analytical approach of 211 employees were used for analysis. Using quantitative analysis: the data were collected through close and open – ended questionnaire coupled with Likert scale. Findings of the study reveals that all three variables; incentive, team work, and employee engagement has a significant influence toward job satisfaction.